2007
DOI: 10.1128/iai.00074-07
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella catarrhalisOuter Membrane Protein CD Elicits Antibodies That Inhibit CD Binding to Human Mucin and Enhance Pulmonary Clearance ofM. catarrhalisin a Mouse Model

Abstract: The outer membrane protein CD of Moraxella catarrhalis is considered to be a potential vaccine antigen against Moraxella infection. We purified the native CD from isolate O35E, administered it to mice, and detected considerable titers of anti-CD antibodies. Anti-CD sera were cross-reactive towards six different M. catarrhalis isolates and promoted bacterial clearance of O35E in a pulmonary challenge model. To circumvent the difficulty of generating large quantities of CD from M. catarrhalis for vaccine use, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 47 publications
(50 reference statements)
5
15
0
Order By: Relevance
“…OMP CD is a heat-modifiable highly conserved porin-like protein (46 kDa) that also plays an important role in the process of adhesion (102). OMP CD functions as an adhesin for both middle ear mucin (84,120) and A549 cells (72). It is anchored in the outer membrane via a ␤-barrel domain, which connects to the C-terminal domain via a linker region.…”
Section: Adhesion and Major Ompsmentioning
confidence: 99%
“…OMP CD is a heat-modifiable highly conserved porin-like protein (46 kDa) that also plays an important role in the process of adhesion (102). OMP CD functions as an adhesin for both middle ear mucin (84,120) and A549 cells (72). It is anchored in the outer membrane via a ␤-barrel domain, which connects to the C-terminal domain via a linker region.…”
Section: Adhesion and Major Ompsmentioning
confidence: 99%
“…Research efforts focusing on the pathogenesis of M. catarrhalis have been hampered largely by the lack of an effective animal model. The system used most often is the mouse pulmonary model, and while this has provided some important data, it is strictly limited to assessing bacterial clearance over a short time frame (5,23,36,40). We have provided data to demonstrate that M. catarrhalis 7169 can colonize the chinchilla NP and persist in these animals for Ͼ2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…MID is an outer-membrane protein (OMP) with specific affinity for soluble and cell-bound human IgD and is the only IgDbinding protein in Moraxella (Forsgren et al, 2001). Several other virulence-associated genes have been identified that may be associated with colonization and infection of M. catarrhalis, including the OMPs CopB, OMPCD, McaP, MhaB, MhaC, Msp22, Msp75, Msp78 and lipooligosaccharide (LOS) Balder et al, 2007;Lipski et al, 2007;Liu et al, 2007;Riesbeck et al, 2006;Ruckdeschel et al, 2008Ruckdeschel et al, , 2009Tan et al, 2006a). Furthermore, several of these virulence genes have also been associated with the induction of the humoral immune response, making them potential vaccine candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…UspA1 and UspA2 acquire their adherence characteristics through multifunctional binding sites, which include domains that have the ability to attach to epithelial cells via cell-associated fibronectin, laminin and vitronectin (Tan et al, 2006b). Furthermore, UspA1 includes a critical binding site for carcinoembryonic antigen-related cell adhesion molecules, which are expressed in various human tissues including respiratory epithelia (Hill & Virji, 2003;Slevogt et al, 2008 Balder et al, 2007;Lipski et al, 2007;Liu et al, 2007;Riesbeck et al, 2006;Ruckdeschel et al, 2008Ruckdeschel et al, , 2009Tan et al, 2006a). Furthermore, several of these virulence genes have also been associated with the induction of the humoral immune response, making them potential vaccine candidate genes.…”
mentioning
confidence: 99%